(untitled) (Revista de Estudos da Linguagem, 2007)
Bertinetto (2001) points out that in spite of the great amount ofresearch and papers developed on the nature of aspectual and temporalrelations in natural languages, the lack of consensus on some verybasic notions related to this topic is still remarkable. The paper byWachowicz, presented at the annual Encontro do GT em Teoria daGramática da ANPOLL, in Ouro Preto, from 1st to 2nd of December,2005 and, later, published in volume 14, number 2 of this magazine,constitutes an interesting attempt to clarify some questions on avery underexplored topic, namely, the aspectual reading in sentenceswith verbal periphrases in which the first verb is an auxiliary. Thispaper discusses Wachowicz’s proposal, raising some questions andmaking some observations on it. It aims at contributing to the researchbeing developed, with the reflections by someone who is not directlyinvolved in it.